Meningkatkan Kualitas Guru Dalam Menguasai TIK Melalui Program Microsoft Partner in Learning (PiL) dan Aplikasi Moodle (Current Research in Education: Conference Series Journal, 2022)
This article aims to determine the competence of teachers in the field of ICT, such as in terms of using, empowering, and innovating technology in learning. It is undeniable that without the expertise and ability to empower this ICT, it has a very big impact on the quality of teachers. The research method we do in solving this problem is by conducting library research without any field research. The results of this study indicate that the quality of teachers in the ICT sector is still low. Therefore, we offer two solutions to solve these problems. the first is by participating in the PIL (Partner In Learning) program and the second is developing online-based learning media in the Moodle (Modular Object-Oriented Dynamic Learning Environment) application. These two solutions are an effort to improve teacher competence in the field of ICT so that they can overcome low teacher quality, such as the PIL program in 2013 which taught millions of teachers in Asia about how to operate good technology and some teachersThose who take part in this program have successfully passed their clueless days and through the Moodle application can make it easier for teachers to innovate related to creative learning media.